Microbiological Assessment of Preservative Methods for African Star Apple (Chrysophyllum albidum Linn) Juice - Chukwumalume, R.C.; Garba, S.A.; Agary, O.O. (Pakistan Journal of Nutrition, 2012)
Microbiological assessment of preservative methods for African Star Apple juice was carried out. The juice samples were subjected to pasteurization, chemical treatment using 0.1% (v/v) sodium benzoate, a combined treatment of both or no treatment. All samples were stored in ambient (28±2oC) or refrigeration (5oC) temperatures for six weeks to determine the effect of treatments on growth count. The juice sample that was pasteurized and preserved with sodium benzoate stored longer than any other sample at both storage conditions. The combination of pasteurization, use of sodium benzoate and juice storage at refrigeration temperature gave the best storage stability.